Supplementary Figure 28 from Clinicopathologic, Genomic, and Immunophenotypic Landscape of ATM Mutations in Non–Small Cell Lung Cancer - Biagio Ricciuti (14951247) (2025)
Supplementary Figure 28. (A) Box-plot showing the distribution of tumor-infiltrating lymphocytes assessed using computational pathology algorithm in ATMMUT and ATMWT NSCLCs. (B) Box-plot showing the distribution of tumor-infiltrating lymphocytes assessed using computational pathology algorithm in according to ATM/TP53 co-mutation status in NSCLC.